Memory retrieval modulates spatial tuning of single neurons in the human entorhinal cortex - Qasim, Salman E. (Nat Neurosci, 2019)
The medial temporal lobe (MTL) is critical for both spatial navigation and memory. While single neurons in the MTL activate to represent locations in the environment during navigation, it remains unclear how this spatial tuning relates to memory for events involving those locations. We examined memory-related changes in spatial tuning by recording single-neuron activity from neurosurgical patients performing a virtual-reality object-location memory task. We identified “memory-trace cells” whose activity was spatially tuned to the retrieved location of the specific object that subjects were cued to remember. Memory-trace cells in the entorhinal cortex (EC), in particular, encoded discriminable representations of different memories through a memory-specific rate code. These findings indicate that single neurons in the human EC change their spatial tuning to target relevant memories for retrieval.